Synthesis and Immobilization of Pt Nanoparticles on Amino-Functionalized Halloysite Nanotubes toward Highly Active Catalysts - Tingting Yang; Mingliang Du; Ming Zhang; Han Zhu; Pan Wang; Meiling Zou (Nanomaterials and Nanotechnology)
A simple and effective method for the preparation of platinum nanoparticles (Pt NPs) grown on amino-func‐ tionalized halloysite nanotubes (HNTs) was developed. The nanostructures were synthesized through the func‐ tionalization of the HNTs, followed by an in situ approach to generate Pt NPs with diameter of approximately 1.5 nm within the entire HNTs. The synthesis process, composition and morphology of the nanostructures were characterized. The results suggest PtNPs/NH2-HNTs nanostructures with ultrafine PtNPs were successfully synthesized by green chemically-reducing H2PtCl6 without the use of surfactant. The nanostructures exhibit promising catalytic properties for reducing potassium hexacyanoferrate(III) to potassium hexacyanoferrate(II). The presented experiment for novel PtNPs/NH2-HNTs nanostructures is quite simple and environmentally benign, permitting it as a potential application in the future field of catalysts.